The Influence of Culturally Responsive Teaching (CRT) Approach Based On Local Wisdom To Increase Environmental Awareness of Fourth Grade Students at Ceger 1 Bogor Public Elementary School in the Science Subject - Rais Hidayat; Septiana Kirani; Rany Nuraningsih (MASI Mandiri Edukasi, 2025)
This research is a quasi-experimental quantitative study. Descriptively, this study aims to describe the increase in environmental awareness of fourth-grade students at Ceger 1 State Elementary School in Bogor who have been learning using a Culturally Responsive Teaching (CRT) approach based on local wisdom and a Scientific Approach. Comparatively, it tests the difference in the increase of environmental awareness among fourth-grade students at Ceger 1 State Elementary School in Bogor between learning using the CRT approach based on local wisdom and the scientific approach. The population of this study consists of all fourth-grade students at Ceger 1 State Elementary School in Bogor, which consists of two classes: class IV A with 17 students and class IV B with 17 students. The data collection technique used a testing instrument in the form of multiple-choice questions for the pretest and posttest, which had been trialled in class V with 19 students. The validity test results of 10 questions yielded a significance value < 0.05, meaning the instrument can be used. The data analysis technique employed descriptive analysis, equivalence tests, normality and homogeneity tests, and hypothesis testing. The results of this study indicate that descriptively, the increase in environmental awareness with the CRT approach obtained an average of 91.76, which falls into the very high category, while environmental awareness using the scientific approach obtained an average of 75.88, which falls into the high category. Comparatively, there is a significant difference in the increased environmental awareness in the class taught using the local wisdom-based CRT and scientific approaches. The t-test results obtained a Sig. (2-tailed) of 0.000 < 0.05. This indicates that the local wisdom-based CRT approach significantly increases environmental awareness more than the scientific approach.